Bibliometrics of Family Law Research Trends in Southeast Asia: An Analysis Two Decades 2003-2023 - Fernando, Henky; Larasati, Yuniar Galuh; Abdullah, Irwan; Firdawaty, Linda; Qodriyah, Khodijatul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Family law has an essential role in ensuring the stability and well-being of society. Conceptually and praxis show that family law has excellent complexity in responding to family problems that continue to develop along with the massive cultural transformation in society. This study aims to identify and evaluate two decades of family law research in Southeast Asia. This study not only uses bibliometric analysis but also utilizes VOSviewers software to visualize the network, trends, and characteristics of family law research in Southeast Asian countries in two decades based on the publication of articles in the Scopus database. Of the 427 published family law research documents in Southeast Asian countries over two decades, Indonesia, Malaysia, and Singapore contributed the most research based on the subject areas of social sciences and arts humanities. However, these studies have been unable to intervene and overcome the problems that arise in marriage, divorce, child custody, and inheritance, which still have the potential to raise various kinds of misconceptions ideologically and praxis. This study also recommends the importance of future studies to analyze the factors and implications of ideological and practical family law misconceptions for family welfare in the future.